Activin A Reduces GIRK Current to Excite Dentate Gyrus Granule Cells - Zheng, Fang; Valero Aracama, Maria Jesus; Schaefer, Natascha; Alzheimer, Christian (Frontiers in Cellular Neuroscience, 2022)
Activin A, a member of the TGF-beta family, is recognized as a multifunctional protein in the adult brain with a particular impact on neuronal circuits associated with cognitive and affective functions. Activin receptor signaling in mouse hippocampus is strongly enhanced by the exploration of an enriched environment (EE), a behavioral paradigm known to improve performance in learning and memory tasks and to ameliorate depression-like behaviors. To interrogate the relationship between EE, activin signaling, and cellular excitability in the hippocampus, we performed ex vivo whole-cell recordings from dentate gyrus (DG) granule cells (GCs) of wild type mice and transgenic mice expressing a dominant-negative mutant of activin receptor IB (dnActRIB), which disrupts activin signaling in a forebrain-specific fashion. We found that, after overnight EE housing, GC excitability was strongly enhanced in an activin-dependent fashion. Moreover, the effect of EE on GC firing was mimicked by pre-treatment of hippocampal slices from control mice with recombinant activin A for several hours. The excitatory effect of activin A was preserved when canonical SMAD-dependent signaling was pharmacologically suppressed but was blocked by inhibitors of ERK-MAPK and PKA signaling. The involvement of a non-genomic signaling cascade was supported by the fact that the excitatory effect of activin A was already achieved within minutes of application. With respect to the ionic mechanism underlying the increase in intrinsic excitability, voltage-clamp recordings revealed that activin A induced an apparent inward current, which resulted from the suppression of a standing G protein-gated inwardly rectifying K+ (GIRK) current. The link between EE, enhanced activin signaling, and inhibition of GIRK current was strengthened by the following findings: (i) The specific GIRK channel blocker tertiapin Q (TQ) occluded the characteristic electrophysiological effects of activin A in both current- and voltage-clamp recordings. (ii) The outward current evoked by the GIRK channel activator adenosine was significantly reduced by preceding EE exploration as well as by recombinant activin A in control slices. In conclusion, our study identifies GIRK current suppression via non-canonical activin signaling as a mechanism that might at least in part contribute to the beneficial effects of EE on cognitive performance and affective behavior.
CRIS-Team WoS Importer:2022-07-01
Keywords: activin; hippocampus; GIRK current; action potential; dentate gyrus granule cells

Dorsal–Ventral Gradient of Activin Regulates Strength of GABAergic Inhibition along Longitudinal Axis of Mouse Hippocampus in an Activity-Dependent Fashion - Valero Aracama, Maria Jesus; Zheng, Fang; Alzheimer, Christian (International Journal of Molecular Sciences, 2023)
The functional and neurophysiological distinction between the dorsal and ventral hippocampus affects also GABAergic inhibition. In line with this notion, ventral CA1 pyramidal cells displayed a more dynamic and effective response to inhibitory input compared to their dorsal counterparts. We posit that this difference is effected by the dorsal–ventral gradient of activin A, a member of the transforming growth factor-β family, which is increasingly recognized for its modulatory role in brain regions involved in cognitive functions and affective behavior. Lending credence to this hypothesis, we found that in slices from transgenic mice expressing a dominant-negative mutant of activin receptor IB (dnActRIB), inhibitory transmission was enhanced only in CA1 neurons of the dorsal hippocampus, where the basal activin A level is much higher than in the ventral hippocampus. We next asked how a rise in endogenous activin A would affect GABAergic inhibition along the longitudinal axis of the hippocampus. We performed ex vivo recordings in wild-type and dnActRIB mice after overnight exposure to an enriched environment (EE), which engenders a robust increase in activin A levels in both dorsal and ventral hippocampi. Compared to control mice from standard cages, the behaviorally induced surge in activin A produced a decline in ventral inhibition, an effect that was absent in slices from dnActRIB mice. Underscoring the essential role of activin in the EE-associated modulation of ventral inhibition, this effect was mimicked by acute application of recombinant activin A in control slices. In summary, both genetic and behavioral manipulations of activin receptor signaling affected the dorsal–ventral difference in synaptic inhibition, suggesting that activin A regulates the strength of GABAergic inhibition in a region-specific fashion.
CRIS-Team Scopus Importer:2023-09-15
Keywords: activin; CA1 pyramidal cell; environmental enrichment; GABA; hippocampus; inhibitory postsynaptic current; tonic GABA current

Environmental enrichment recruits activin A to recalibrate neural activity in mouse hippocampus - Dahlmanns, Marc; Dahlmanns, Jana; Schmidt, Carla C.; Valero Aracama, Maria Jesus; Zheng, Fang; Alzheimer, Christian (Cerebral Cortex, 2022)
The TGF-beta family member activin A modulates neural underpinnings of cognitive and affective functions in an activity-dependent fashion. We have previously shown that exploration of a novel and enriched environment (EE) strongly enhanced activin signaling. Whereas the many beneficial effects of EE are amply documented, the underlying mechanisms remain largely elusive. Here, we examined the hypothesis that EE recruits activin to regulate synaptic plasticity in a coordinated, cognition-promoting manner. Elevated activin levels after EE enhanced CA1 pyramidal cell excitability, facilitated synaptic transmission, and promoted long-term potentiation. These EE-induced changes were largely absent in mice expressing a dominant-negative mutant of activin receptor IB. We then interrogated the impact of activin on network oscillations and functional connectivity, using high-speed Ca (2+) imaging to study spike routing within networks formed by dissociated primary hippocampal cultures. Activin facilitated Ca2+ signaling, enhanced the network strength, and shortened the weighted characteristic path length. In the slice preparation, activin promoted theta oscillations during cholinergic stimulation. Thus, we advance activin as an activity-dependent and very early molecular effector that translates behavioral stimuli experienced during EE exposure into a set of synchronized changes in neuronal excitability, synaptic plasticity, and network activity that are all tuned to improve cognitive functions.
CRIS-Team WoS Importer:2022-03-25
Keywords: brain slice; hippocampal culture; network oscillations; neuronal connectivity; synaptic plasticity

Sox11 is an Activity-Regulated Gene with Dentate-Gyrus-Specific Expression Upon General Neural Activation - von Wittgenstein, Julia; Zheng, Fang; Wittmann, Marie-Theres; Balta, Elli-Anna; Ferrazzi, Fulvia; Schäffner, Iris; Häberle, Benjamin; Valero Aracama, Maria Jesus; Koehl, Muriel; Miranda, Carlos J.; Kaspar, Brian K.; Ekici, Arif Bülent; et al. (Cerebral Cortex, 2020)
Neuronal activity initiates transcriptional programs that shape long-term changes in plasticity. Although neuron subtypes differ in their plasticity response, most activity-dependent transcription factors (TFs) are broadly expressed across neuron subtypes and brain regions. Thus, how region- and neuronal subtype-specific plasticity are established on the transcriptional level remains poorly understood. We report that in young adult (i.e., 6-8 weeks old) mice, the developmental TF SOX11 is induced in neurons within 6 h either by electroconvulsive stimulation or by exploration of a novel environment. Strikingly, SOX11 induction was restricted to the dentate gyrus (DG) of the hippocampus. In the novel environment paradigm, SOX11 was observed in a subset of c-FOS expressing neurons (ca. 15%); whereas around 75% of SOX11+ DG granule neurons were c-FOS+, indicating that SOX11 was induced in an activity-dependent fashion in a subset of neurons. Environmental enrichment or virus-mediated overexpression of SOX11 enhanced the excitability of DG granule cells and downregulated the expression of different potassium channel subunits, whereas conditional Sox11/4 knock-out mice presented the opposite phenotype. We propose that Sox11 is regulated in an activity-dependent fashion, which is specific to the DG, and speculate that activity-dependent Sox11 expression may participate in the modulation of DG neuron plasticity.
CRIS-Team Scopus Importer:2020-05-29
Keywords: dentate gyrus; hippocampus; immediate early gene; plasticity; Sox11